Millenial Generations’ Awareness of Halal Supply Chain and Related Food Product in Malaysia - OSMAN, LOKHMAN HAKIM; bt Aziz, Riadhus Solehah (Universitas Negeri Semarang, 2019)
Muslim consumers especially in this millennial generation must ensure that the all supply chains food product they consume must meet halal requirements under Islamic law. Now days millennial generation more aware and concern about the integrity of halal status and also always curious about the processes and activities involved along the supply chain whether the products that they purchased were very truly Halal until end of consumption. This study seeks and examines questionnaire data from which 14 ? 35 years old of millennial generations with convenience sampling where 150 consumers of halal food products with the aims to determine the extent which millennial generations? are aware of halal principles.  In addition to that, this research will also seek to determine the determinant that may affects their behavior and conducts towards halal supply chain.  A survey was conducted towards halal supply chain in Malaysia. The results of this study suggested that millennial generations are increasingly aware of the halal supply chains and the advantage of halal supply chains. This study has provided exposure new insights for business owners/consumers or practitioners and policy makers whose decisions might give impact not only in halal supply chains industry but also to economic advantages.